Comparative analysis of various laboratory biomarkers based on the severity of COVID-19 in a tertiary care hospital in South India - Karthick Elango; Sathya Selvarajan; Sowmya Krishnamurthy (JURNAL INDONESIA DARI ILMU LABORATORIUM MEDIS DAN TEKNOLOGI, 2024)
COVID-19 (Corona Virus Disease 2019) was a life-changing pandemic with impact on social, environmental, health, and economic issues. Various inflammatory and hematological biomarkers studied individually or in combination in the literature have shown significant results with regard to COVID-19 pathology, severity, and prognosis. Yet the question of interest is how covid-19 inflammatory cascade impacts the interlink between the biomarkers during different stages. This study aims to retrospectively analyse ferritin, albumin, alanine aminotransferase (ALT), aspartate aminotransferase (AST), total bilirubin, direct bilirubin, blood urea nitrogen (BUN), creatinine, D-dimer, Lactate Dehydrogenase (LDH), C Reactive Protein (CRP) and Interleukin-6 (IL-6) levels between two groups based on COVID-19 severity.  A retrospective cross-sectional study was conducted with laboratory data of COVID-19 patients admitted at Sri Ramachandra Medical College Hospital, India. The sample size was 104 [Group1: severe disease, n=52; Group-2: mild disease, n=52]. After normality testing, data were compared between the two groups followed by correlation analysis between the variables. A p<0.05 was considered statistically significant. On comparison, Group 2 (severe COVID-19 disease) showed significant difference in the levels of all the biomarkers (p<0.005) except Creatinine (p<0.128) when compared with Group 1 (mild COVID-19 disease). Significant correlation was obtained between all biomarkers (p<0.005) except creatinine. The correlation analysis primarily explains the inflammatory cascade involved in disease. Ferritin appears to have a standalone effect on disease severity, progression, organ dysfunction. This understanding can be used to provide better and more timely care.